2006
DOI: 10.1097/ftd.0b013e31802bfd69
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Digoxin Cross-Reacting Substances in Patients With Acute Yellow Oleander (Thevetia peruviana) Poisoning, Including the Effect of Activated Charcoal

Abstract: Intentional self-poisonings with seeds from the yellow oleander tree (Thevetia peruviana) are widely reported. Activated charcoal has been suggested to benefit patients with yellow oleander poisoning by reducing absorption and/or facilitating elimination. Two recent randomised controlled trials (RCTs) assessing the efficacy of activated charcoal reported conflicting outcomes in terms of mortality. The effect of activated charcoal on the pharmacokinetics of Thevetia cardenolides has not been assessed. This info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
1
34
1
1
Order By: Relevance
“…13,14 Recently, the pharmacokinetics of digoxin cross-reacting substances in patients poisoned with oleander was studied using the FPIA for digoxin. 18 In recent years, the use of complementary and herbal medicines has become more popular with the general population and several herbal products also contain oleander extract. Oleander extract has been shown to have selective cytotoxicity to tumor cells as opposed to normal cells, and Anvirzel (Ozelle Pharmaceuticals, San Antonio, TX), a patented medicine prepared from oleander, is in a clinical trial as a potential anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recently, the pharmacokinetics of digoxin cross-reacting substances in patients poisoned with oleander was studied using the FPIA for digoxin. 18 In recent years, the use of complementary and herbal medicines has become more popular with the general population and several herbal products also contain oleander extract. Oleander extract has been shown to have selective cytotoxicity to tumor cells as opposed to normal cells, and Anvirzel (Ozelle Pharmaceuticals, San Antonio, TX), a patented medicine prepared from oleander, is in a clinical trial as a potential anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these symptoms, patients can also present with cardiac arrhythmias ranging from sinus bradycardia to third degree atrioventricular block 3 4. These effects are derived from the structural and chemical similarities between the yellow oleander cardenolide-oleandrin and digitalis cardenolides derived from foxglove 5. These chemical similarities allow for some cross reactivity and detection by immunoassays utilised for measuring serum digoxin levels, with variable sensitivities 6 7.…”
Section: Discussionmentioning
confidence: 99%
“…These chemical similarities allow for some cross reactivity and detection by immunoassays utilised for measuring serum digoxin levels, with variable sensitivities 6 7. Ingestion of any part of the plant can result in poisoning with variable pharmacokinetics depending on the cardiac glycoside concentration of the different parts of the plant and the time following ingestion 3 5. There are reports of poisonous ingestion ranging from herbal teas to ingestion of a meal containing snail stew from a snail tissue with traces of oleandrin 8 9.…”
Section: Discussionmentioning
confidence: 99%
“…The effi cacy of digoxin -specifi c Fab fragments for yellow oleander poisoning is variable, with improvement of the cardiac abnormalities in some, but not all patients with serious yellow oleander poisoning. 51 59 Her rhythm did not revert to normal sinus rhythm until 16 hours after ingestion despite the administration of an additional 190 mg digoxin -specifi c Fab antibody fragments.…”
Section: Treatmentmentioning
confidence: 99%
“…51 The apparent terminal half -life of Thevetia cardenolides as estimated by a digoxin immunoassay in patients receiving supportive care and no activated charcoal was also highly variable with a median time of 42.9 hours (range: 13.27 -94.24 hours). Toxicokinetic data from a clinical study of 104 patients with Thevetia intoxication indicated that the absorption of Thevetia cardenolides is highly variable and prolonged with the time to maximum concentration exceeding 24 hours in some patients.…”
Section: Toxicokineticsmentioning
confidence: 99%